A cross-linguistic comparison of clausal embedding with causative and perception verbs - Lorusso, Paolo; Badan, Linda (Isogloss, 2024)
In Italian, causatives are expressed through a periphrasis make + infinitival V. When the embedded verb is transitive, the embedded subject is generally introduced by a to/by preposition. For this reason, some scholars have analyzed causatives as a verbal complex with a single argument structure, involving a complex functional layer. In this paper, we offer a cross-linguistic comparison of causative clausal embedding. First, we compare Italian causatives with perception verbs, where no prepositions introduce the embedded subject. Then, we compare Italian causatives to those in Balkan languages and Southern Italian varieties which allow finite embedding. We account for the variation in terms of differences in the (+/-) defective status of the embedded clause and in the availability of AGREE operation (inspired by Manzini 2022). We conclude the comparison with Chinese, where no AGREE operation is available and a θ-feature checking operation is at work: embedded subjects check the θ-feature of both verbs as in the control construction (à la Manzini & Roussou2000). We argue that language variation in clausal embeddings relates to the phasal/non phasal status of embedded clauses and to the available syntactic operations.